2006
DOI: 10.1038/nrd2083
|View full text |Cite
|
Sign up to set email alerts
|

Applications of ESI-MS in drug discovery: interrogation of noncovalent complexes

Abstract: For many years, analytical mass spectrometry has had numerous supporting roles in the drug development process, including the assessment of compound purity; quantitation of absorption, distribution, metabolism and excretion; and compound-specific pharmacokinetic analyses. More recently, mass spectrometry has emerged as an effective technique for identifying lead compounds on the basis of the characterization of noncovalent ligand-macromolecular target interactions. This approach offers several attractive prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
218
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(219 citation statements)
references
References 92 publications
(99 reference statements)
0
218
0
1
Order By: Relevance
“…metallodrugprotein adducts. Although ESI MS is not a quantitative technique, it can be used to screen multicomponent systems, providing a semiquantitative description of the abundance of the species in solution [42]. Typically, ESI MS has been applied to establish the affinity of multiple potential ligands for a single macromolecular target; however, related procedures have been used to study ligand binding to (and affinity for) a protein mixture [38].…”
Section: Resultsmentioning
confidence: 99%
“…metallodrugprotein adducts. Although ESI MS is not a quantitative technique, it can be used to screen multicomponent systems, providing a semiquantitative description of the abundance of the species in solution [42]. Typically, ESI MS has been applied to establish the affinity of multiple potential ligands for a single macromolecular target; however, related procedures have been used to study ligand binding to (and affinity for) a protein mixture [38].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on experimental conditions and nature of the complex, a time window of Ϸ10 Ϫ3 s can be available for complex detection in the mass spectrometer. Then ESI MS can give information on complex stoichiometry and, after complex dissociation (MS/MS), reveal the identity of binding partners (6)(7)(8)(9)(10)(11).…”
Section: Gaseous Protein Complexesmentioning
confidence: 99%
“…to time-of-flight mass spectrometry (ToF-MS) [31,32,35]. ESI-MS n studies of antimalarial compounds as bisthiazolium or quinolines can be found on reports by Nicolas et al [38] or Smyth et al and O'Donnell et al [34,39], respectively.…”
Section: Introductionmentioning
confidence: 99%